Compliance as a Necessary Element of Legal Regulation of Environmental Relations - D. M. Dubovik (Теоретическая и прикладная юриспруденция)
The article analyzes the issues of introducing the institution of environmental compliance by business entities as a necessary and important process in the development of green entrepreneurship.As a problem, the author highlights the lack of a system of legal incentives for enterprises that rationally use natural resources in their economic activities (environmental entrepreneurship).Turning to the issue of legal regulation of environmental compliance, the author paid attention to the legal nature of this institution, identified possible legislative measures to stimulate enterprises that develop,  implement and operate environmental compliance.Considering the issue of legal regulation of environmental compliance, special attention is paid to the introduction of this institution within the framework of the reform of control and supervisory activities, the process of its development in terms of shifting the focus from supervisory measures to preventive measures.